Legal Protection for Defendants with Disabilities (Decision Study: 146/PID.SUS/2025/PT MTR) - Naira, Reva; Prasetyo , Boedi (Journal of Public Representative and Society Provision, 2025)
This study examines legal protection for defendants with disabilities in the Indonesian criminal justice system, with reference to Decision 146/PID.SUS/2025/PT.MTR. Using a normative legal research approach, this research analyzes relevant laws and regulations, international legal instruments, and court decisions to assess the implementation of the principle of presumption of innocence and the right to a fair trial for persons with disabilities. The study focuses on the application of Law Number 8 of 2016 concerning Persons with Disabilities and related regulations on reasonable accommodation in judicial proceedings. The findings indicate that, although legal provisions guarantee equal treatment, accessibility, and procedural protection for defendants with disabilities, their practical implementation remains limited. In the examined case, deficiencies were identified in the provision of communication assistance, procedural adjustments, and supportive services during the trial process. These limitations affected the defendant’s ability to participate effectively in legal proceedings. The study concludes that greater institutional commitment, improved professional capacity among law enforcement officials, and stronger supervision mechanisms are necessary to ensure the fulfillment of disability rights in criminal trials. Strengthening the implementation of reasonable accommodation is essential to achieve fairness, transparency, and legal certainty in the administration of justice for defendants with disabilities.